2016
DOI: 10.1177/0956797615627625
|View full text |Cite|
|
Sign up to set email alerts
|

When Is an Adolescent an Adult? Assessing Cognitive Control in Emotional and Nonemotional Contexts

Abstract: An individual is typically considered an adult at age 18, although the age of adulthood varies for different legal and social policies. A key question is how cognitive capacities relevant to these policies change with development. The current study used an emotional go/no-go paradigm and functional neuroimaging to assess cognitive control under sustained states of negative and positive arousal in a community sample of one hundred ten 13- to 25-year-olds from New York City and Los Angeles. The results showed di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
188
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 218 publications
(229 citation statements)
references
References 42 publications
11
188
0
4
Order By: Relevance
“…This is consistent with studies showing that adolescents have difficulty suppressing attention and actions toward emotional stimuli even when these are irrelevant to the task at hand (Grose-Fifer, Rodrigues, Hoover, & Zottoli, 2013). Since habituation of the subcortical regions (including amygdala and ventral striatum) appears to be coupled with VMPFC activity (Grimshaw & Carmel, 2014;Hare et al, 2008), it is possible that the increased impulsivity in response to emotional stimuli in adolescents is due to less mature prefrontal top-down regulation of these subcortical regions (Casey, 2015;Cohen et al, 2016).…”
Section: Impulsivity In Adolescence: Neuropsychological Researchsupporting
confidence: 78%
See 2 more Smart Citations
“…This is consistent with studies showing that adolescents have difficulty suppressing attention and actions toward emotional stimuli even when these are irrelevant to the task at hand (Grose-Fifer, Rodrigues, Hoover, & Zottoli, 2013). Since habituation of the subcortical regions (including amygdala and ventral striatum) appears to be coupled with VMPFC activity (Grimshaw & Carmel, 2014;Hare et al, 2008), it is possible that the increased impulsivity in response to emotional stimuli in adolescents is due to less mature prefrontal top-down regulation of these subcortical regions (Casey, 2015;Cohen et al, 2016).…”
Section: Impulsivity In Adolescence: Neuropsychological Researchsupporting
confidence: 78%
“…Given that affective, bottom-up processes are often regulated by the top-down cognitive processes discussed above, it may be difficult to determine whether impulsive behaviors that appear in combination with affective/motivational impairments are in fact caused directly by the socioemotional system or indirectly, as a result of decreased regulation by the cognitive control system. However, as impulsive behaviors are known to occur when neuropsychological evidence of cognitive deficits is absent, it stands to reason that deficits in affective/motivational processes can directly trigger impulsive behaviors (Bechara, 2005;Casey, 2015;Cohen et al, 2016). This possibility is strengthened by neuroimaging studies (e.g., McClure, Laibson, Loewenstein, & Cohen, 2004) that link activity in the OFC, medial PFC, limbic and paralimbic cortical structures, but not DLPFC and parietal areas, specifically to impulsive choices.…”
Section: The Proposed Model: Affective and Cognitive Impulsivitymentioning
confidence: 93%
See 1 more Smart Citation
“…A second reason to suspect that mPFC underlies negative affect-specific changes in development comes from prior work showing that mPFC responses to aversive stimuli change in qualitative and striking ways across development (Cohen et al, 2016). With regards to vmPFC, prior neuroimaging studies have revealed that vmPFC responses to aversive stimuli decrease during adolescence (McRae et al, 2012), and that functional connectivity between vmPFC and the amygdala in response to aversive stimuli is initially positive but becomes negative during the transition from childhood to adolescence (Gee et al, 2013; Silvers et al, in press).…”
mentioning
confidence: 99%
“…Such work suggests that vmPFC responses to aversive stimuli generally decrease with age but also that the way in which vmPFC and the amygdala interact changes as well. In contrast to vmPFC, dmPFC responses to aversive stimuli increase steadily from early adolescence and into adulthood (Cohen et al, 2016; Williams et al, 2006). As such, we hypothesized that in the present study age would be associated with a simultaneous decrease in vmPFC recruitment and increase in dmPFC recruitment in response to aversive (but not neutral) stimuli.…”
mentioning
confidence: 99%